2019
DOI: 10.2174/1573406414666180829150515
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil from Lippia origanoides (Verbenaceae): Haemostasis and Enzymes Activity Alterations

Abstract: The results obtained in this work amplify the pharmacological characterization of the essential oil from L. origanoides. However, new studies are fundamental to define the action mechanisms and determine pharmaceutical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…This improvement could be related to various enzymes such as protease, amylase, and cellulase secreted by gastrointestinal tract, which were produced by BS or EO stimulation. (Attia et al 2015(Attia et al , 2017(Attia et al , 2019Li et al 2018;Teixeira et al 2019;Krauze et al 2020). Additionally, it has been shown that BS or EO supplementation can improve gut morphology, increase the population of beneficial gut microflora, thereby increasing the efficiency of nutrient utilisation (Mousavi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement could be related to various enzymes such as protease, amylase, and cellulase secreted by gastrointestinal tract, which were produced by BS or EO stimulation. (Attia et al 2015(Attia et al , 2017(Attia et al , 2019Li et al 2018;Teixeira et al 2019;Krauze et al 2020). Additionally, it has been shown that BS or EO supplementation can improve gut morphology, increase the population of beneficial gut microflora, thereby increasing the efficiency of nutrient utilisation (Mousavi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…El dispositivo de extracción incluye una fuente de calentamiento, un condensador y un decantador para recoger el condensado y separar el AE del agua, respectivamente (Jurevičiūtė et al, 2019). A escala industrial, este método todavía se utiliza debido a la simplicidad de las instalaciones (no requiere equipos costosos), facilidad de implementación del método y selectividad (Teixeira et al, 2019).…”
Section: Hidrodestilaciónunclassified
“…La extracción se realiza dentro de un matraz con calentamiento, que tiene un sistema de placa perforada o rejilla que mantiene la planta suspendida sobre la base del destilador, el cual contiene agua que evita su contacto directo (Teixeira et al, 2019). La extracción se realiza mediante la inyección de vapores de agua, que atraviesan la materia vegetal de abajo hacia arriba y transportan los materiales volátiles.…”
Section: Hidrodestilación De Vaporunclassified
“…However, the investigations of the antibacterial activity of many essential oils, plants aquatic and alcoholic extracts has been done, and many of them proved their strong antibacterial activity. In alternative medicine, plant extracts and essential oils have been reported to have hemostasis ability as well as antimicrobial and antioxidant activity [ 165 ]. Antibacterial cellulose-based edible films have been fabricated for food packaging applications by using thyme essential oil as an antibacterial ingredient inside the film [ 166 ].…”
Section: Challenges and Propositions Of Biopolymer-based Antibactementioning
confidence: 99%